The Obese Brain: Mechanisms of Systemic and Local Inflammation, and Interventions to Reverse the Cognitive Deficit - Salas-Venegas, Verónica; Flores-Torres, Rosa Pamela; Rodríguez-Cortés, Yesica María; Rodríguez-Retana, Diego; Ramírez-Carreto, Ricardo Jair; Concepción-Carrillo, Luis Edgar; Pérez-Flores, Laura Josefina; Alarcón-Aguilar, Adriana; López-Díazguerrero, Norma Edith; Gómez-González, Beatriz; Chavarría, Anahí; Konigsberg, Mina (Frontiers in Integrative Neuroscience, 2022)
Overweight and obesity are now considered a worldwide pandemic and a growing public health problem with severe economic and social consequences. Adipose tissue is an organ with neuroimmune-endocrine functions, which participates in homeostasis. So, adipocyte hypertrophy and hyperplasia induce a state of chronic inflammation that causes changes in the brain and induce neuroinflammation. Studies with obese animal models and obese patients have shown a relationship between diet and cognitive decline, especially working memory and learning deficiencies. Here we analyze how obesity-related peripheral inflammation can affect central nervous system physiology, generating neuroinflammation. Given that the blood-brain barrier is an interface between the periphery and the central nervous system, its altered physiology in obesity may mediate the consequences on various cognitive processes. Finally, several interventions, and the use of natural compounds and exercise to prevent the adverse effects of obesity in the brain are also discussed.